Volatility linkages between price returns of Crude oil and crude palm oil in the ASEAN region: A copula based GARCH approach - Teera Kiatmanaroch (2018)
© Springer International Publishing Switzerland 2015. This paper used the copula based ARMA-GARCH to examine the dependence structure between the weekly prices of two commodities, namely Crude oil and Crude palm oil. We found evidence of a weak positive dependence between two commodities prices. These findings suggest that the crude oil market of the Middle East and the crude palm oil market of Malaysia are linked together. This information is useful for decision making in various area, such as the risk management in financial field and the international trade in agricultural commodities.